KOMBINASI RANK ORDER CENTROID (ROC) DAN MULTI ATTRIBUTE UTILITY THEORY (MAUT) UNTUK SELEKSI CALON PENERIMA KIP-KULIAH - Chaurina, Agfanadita Rezkia; Rahajoe, Ani Dijah; Nurlaili, Afina Lina (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The low participation rate in higher education in Indonesia remains a major challenge, particularly among students from underprivileged socioeconomic backgrounds. Programs such as KIP-Kuliah are part of the government's efforts to expand educational access, although various implementation challenges persist. At Universitas Pembangunan Nasional “Veteran” Jawa Timur, the number of KIP-Kuliah applicants consistently exceeds the available quota each year, necessitating a selection system that supports fair and accurate decision-making. This study aims to develop a web-based decision support system to assist in the selection process of KIP-Kuliah recipients more systematically. The method combines Rank Order Centroid (ROC) to assign weights to each criterion based on priority ranking and Multi-Attribute Utility Theory (MAUT) to calculate the final score for each alternative. The ranking results are then adjusted according to the recipient quota set for each study program accreditation. Evaluation results show that the system achieved a 96.67% accuracy rate compared to the institution’s manual selection results, indicating its effectiveness in supporting decision-making that is objective, efficient, and transparent.